Through Traditional Music Sarone and Cultural Learning in an Educational Context - Alfandi Al Ansori; Hary Murcahyanto; Yuspianal Imtihan; Alwan Hafiz (Sumber Belajar Sejahtera, 2023)
This research aims to describe the sacredness of Sarone music in wedding ceremonies within the Tanjung Luar village community, Keruak Subdistrict, East Lombok Regency. The research employs a qualitative ethnographic method. Data collection is carried out through literature review, observation, interviews, and documentation. Data are analyzed through data reduction, data presentation, and conclusion. To ensure data validity, triangulation techniques are utilized. The research findings reveal that the sacredness of Sarone music in wedding ceremonies in Tanjung Luar village encompasses elements such as origins, rituals, Sarone heirlooms, taboos, instruments, songs, and Mancak. Sarone music is considered a form of respect for ancestors, a link to cultural heritage, a means of preserving tradition's sanctity, and an integral part of the cultural identity of the Tanjung Luar village community. While the community has diverse perspectives, they all emphasize the importance of maintaining the strong tradition and cultural values associated with Sarone music. In conclusion, Sarone music possesses sacred elements like its history, heirlooms, taboos, instruments, songs, and Mancak dance, which create a sacred atmosphere and are used in the sequence of wedding events and rituals as a form of tribute to ancestors and the preservation of the cultural identity of the Tanjung Luar village community.